2022
DOI: 10.3389/fnut.2022.841444
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sensory Properties in Moderating Eating Behaviors and Food Intake

Abstract: Sensory properties inform likes and dislikes, but also play an important functional role in guiding food choice and intake behavior. Odors direct food choice and stimulate sensory-specific appetites and taste helps to anticipate calorie and nutrient content of food. Food textures moderate eating rate and the energy consumed to satiation and post-ingestive metabolism. We summarize how sensory cues moderate intake, and highlight opportunities to apply sensory approaches to improve dietary behavior. Salt, sweet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 74 publications
(87 reference statements)
0
29
0
1
Order By: Relevance
“…A number of sensory studies (i.e., taste perception and/or preference studies) have been conducted in relation to food choice and dietary intake in different age groups (12)(13)(14)(15)(16)(17). Sweet, salty and savory tastes have been shown to influence energy intake (18). In our previous systematic review of adolescents' taste perception and food choices, we found that perceived bitterness in cruciferous vegetables (i.e., broccoli, cabbage, Brussels sprouts and cauliflower) was negatively associated with intake and preferences and positively associated with energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…A number of sensory studies (i.e., taste perception and/or preference studies) have been conducted in relation to food choice and dietary intake in different age groups (12)(13)(14)(15)(16)(17). Sweet, salty and savory tastes have been shown to influence energy intake (18). In our previous systematic review of adolescents' taste perception and food choices, we found that perceived bitterness in cruciferous vegetables (i.e., broccoli, cabbage, Brussels sprouts and cauliflower) was negatively associated with intake and preferences and positively associated with energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…Future dietary interventions may consider opportunities to moderate eating rate and intake behavior by changing food texture, while also optimizing nutrient absorption with an enhanced matrix structure. Research has shown that hedonically equivalent food textures can be used to reduce earing rate and energy intake, with estimates suggesting a 20% reduction in eating rate is associated with decreases of 10–14% in ad libitum intake [ 33 ]. Future research is now needed to demonstrate the sustained efficacy of these texture-based approaches beyond the current short-term feeding trials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the large differences between liquids and solid foods, the texture of solid and semi-solid foods has been shown to influence the eating rate and energy intake [ 33 , 34 ]. Texture properties influence the oro-sensory exposure time, average bite/sip size, and number of chews per bite and through this meal eating rate (g/min) and energy intake rate (kcal/min) during consumption.…”
Section: Food Texture Oral Processing Eating Rate and Energy Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals identifying as Hispanics and African-Americans are found to rate various taste intensities (sweet, salty, sour, and bitter) higher than non-Hispanics with more notable differences being apparent in males than females (15). Since sensory properties appear to determine food choices and intake (2), these could potentially play a role in the diet-related disparities among racial and ethnic minority groups (17). In addition, there are documented differences in food choices by gender.…”
Section: Introductionmentioning
confidence: 99%